2015
DOI: 10.1111/1467-8489.12099
|View full text |Cite
|
Sign up to set email alerts
|

Improving value transfer through socio-economic adjustments in a multicountry choice experiment of water conservation alternatives

Abstract: This study tests the transferability of the nonmarket values of water conservation for domestic and environmental purposes across three south European countries and Australia applying a common choice experiment design. Different approaches are followed to test the transferability of the estimated values, aiming to minimise transfer errors for use in policy analysis, comparing both single-and multicountry transfers, with and without socio-economic adjustments. Within Europe, significant differences are found be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Moreover, given that most studies are concentrated in a small handful of developed countries, analysts may wish to transfer values across borders. However, as recent studies that have conducted international benefits transfers have shown, there remain numerous questions about the best manner in which to conduct these types of transfers to minimize transfer error (Lindhjem and Navrud, 2008;Brouwer et al, 2015).…”
Section: Applying Ter Marine Species Values To Policymentioning
confidence: 99%
“…Moreover, given that most studies are concentrated in a small handful of developed countries, analysts may wish to transfer values across borders. However, as recent studies that have conducted international benefits transfers have shown, there remain numerous questions about the best manner in which to conduct these types of transfers to minimize transfer error (Lindhjem and Navrud, 2008;Brouwer et al, 2015).…”
Section: Applying Ter Marine Species Values To Policymentioning
confidence: 99%
“…The WFD allows derogations from 'good ecological status' where remediation projects may be technically infeasible, or where remediation costs may be disproportionate to the benefits created (Article 4, par. 4,5,7). The financial costs of pollution remediation must be offset against the benefits of that remediation.…”
Section: Introductionmentioning
confidence: 99%
“…The class 6 Price, High Recreational Quality and RQ*EQ variables have heterogeneous variance within the CL model. 7 Latent class model generated using Latent Gold 5 [46]. membership covariates capture the impact of observables on class membership probabilities.…”
Section: Latent Class Resultsmentioning
confidence: 99%
“…The WFD allows derogations from 'good ecological status' where remediation projects may be technically infeasible or remediation costs may be disproportionate to the benefits created (article 4, par. 4,5,7). The financial costs of pollution remediation must be offset against the benefits of that remediation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation